Leukemia therapy by flavonoids: Future and involved mechanisms. Issue 6 (30th November 2018) - Saraei, Raedeh; Marofi, Faroogh; Naimi, Adel; Talebi, Mehdi; Ghaebi, Mahnaz; Javan, Naser; Salimi, Omid; Hassanzadeh, Ali
Abstract: Flavonoids are a varied family of phytonutrients (plant chemicals) usually are detected in fruits and vegetables. In this big family, there exist more than 10, 000 members that is separated into six chief subtypes: isoflavonols, flavonoenes, flavones, flavonols, anthocyanins, and chalcones. The natural compounds, such as fruits, have visible positive effects in regulating of survival involved signaling pathways that performance as the regulator of cell survival, growth, and proliferation. Researchers have established that commonly consumption up flavonoids decreases incidence and development risk of certain cancers, especially leukemia. Flavonoids have been able to induce apoptosis and stimulate cell cycle arrest in cancer cells via different pathways. Similarly, they have antiangiogenesis and antimetastasis capability, which were shown in wide ranges of cancer cells, particularly, leukemia. It seems that flavonoid because of their widespread approval, evident safety and low rate of side effects, have hopeful anticarcinogenic potential for leukemia therapy. Based on the last decade reports, the most important acting mechanisms of these natural compounds in leukemia cells are stimulating of apoptosis pathways by upregulation of caspase 3, 8, 9 and poly ADP‐ribose polymerase (PARP) and proapoptotic proteins, particularly Bax activation. As well, they can induce cell cycle arrest in target cells not only via increasing of activated levels of p21 and p53 but also by inhibition of cyclins and cyclin‐dependent kinases. Furthermore, attenuation of neclear factor‐κB and signal transducer and activator of transcription 3 activation, suppression of signaling pathway and downregulation of intracellular antiapoptotic proteins are other significant antileukemic function mechanism of flavonoids. Overall, it appears that flavonoids are promising and effective compounds in the field of leukemia therapy. In this review, we tried to accumulate and revise most promising flavonoids and finally declared their major working mechanisms in leukemia cells. Abstract : In this review, we tried to accumulate and revise most promising flavonoids and finally declared their major working mechanisms in leukemia cells.